Design and development of a virtual model of an electric vehicle of category L7. (July 2019) - Pappalardo, C M; Lombardi, N; Dašić, P V; Guida, D
Abstract: This study is aimed at creating an accurate mathematical model, developed in Matlab-Simulink through the Simscape library, concerning an electric vehicle of class L7. To this end, a mechanical model with three degrees of freedom is used. The degrees of freedom are advancement, vertical displacement, and pitch. Two degrees of freedom are also added to this dynamical model in order to model the stiffness and the damping of the tires, whose behavior is described by the "Magic Formula". The propulsion unit is modeled in a standard design configuration. The vehicle can be controlled by supplying the driver's inputs, by controlling the cruising speed, or by ensuring that the vehicle has a driving cycle. The proposed model allows for identifying the critical aspects of the selected design solution, thereby reducing the time required in the design phases.